MUC21: a new target for tumor treatment - Li, Miao; Li, Hui; Yuan, Ting; Liu, Zhi; Li, Yukun; Tan, Yingzheng; Long, Yunzhu (Frontiers in Oncology, 2024)
MUC21, also known as Epiglycanin, is a high-molecular-weight glycoprotein with transmembrane mucin properties. It consists of a tandem repeat domain, a stem domain, a transmembrane domain and a cytoplasmic tail. MUC21 is expressed is observed in normal tissues in organs like the thymus, testes, lungs, and large intestine.Research has shown that MUC21 is expressed in esophageal squamous cell carcinoma, lung adenocarcinoma, glioblastoma, thyroid cancer, melanoma, and various other malignant tumors in distinctive manner. Additionally, tumor invasion, metastasis, and poor prognosis are linked to it. Some researchers believe that MUC21 has the potential to become a new target in cancer treatment. This review aims to deliver a comprehensive overview of the glycosylation, function, and research progress of MUC21 in multiple types of cancer and infectious diseases.